2013
DOI: 10.1155/2013/292158
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Retinal Nerve Fiber Layer Thickness in Patients with Obstructive Sleep Apnea Syndrome

Abstract: Aim. To evaluate the retinal nerve fiber layer (RNFL) thickness in patients with obstructive sleep apnea syndrome (OSAS) by optical coherence tomography (OCT). Materials and Method. We studied 43 new diagnosed OSAS patients and 40 healthy volunteers. Patients underwent an overnight sleep study in an effort to diagnose and determine the severity of OSAS. RNFL analyses were performed using Stratus OCT. The average and the four-quadrant RNFL thickness were evaluated. Results. There was no difference between the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
3
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 30 publications
2
33
3
4
Order By: Relevance
“…However, the results of studies using OCT to compare the RNFL thickness in patients with OSAHS and healthy controls have been inconsistent. Some studies reported a decrease in RNFL thickness in patients with OSAHS [7,9,10], whereas others found no statistically significant difference in RNFL thickness [11,12]. The aim of this study was to use a meta-analysis to evaluate changes in RNFL thickness in patients with OSAHS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of studies using OCT to compare the RNFL thickness in patients with OSAHS and healthy controls have been inconsistent. Some studies reported a decrease in RNFL thickness in patients with OSAHS [7,9,10], whereas others found no statistically significant difference in RNFL thickness [11,12]. The aim of this study was to use a meta-analysis to evaluate changes in RNFL thickness in patients with OSAHS.…”
Section: Introductionmentioning
confidence: 99%
“…Degeneration after ischemia causes thinning of the RNFL. Adam, et al [33] reported that RNFL thickness was not different between the control and OSAS groups. Moghimi, et al [34] suggested that thinning of the RNFL has been associated with elevated intraocular pressure.…”
Section: Discussionmentioning
confidence: 95%
“…Thinning of RNFL may be related to ageing or may accompany ocular disorders. Histopathological studies reported RNFL thinning in various systemic diseases [33].…”
Section: Discussionmentioning
confidence: 99%
“…43 OUAS'lu ve 40 kontrol hastasının MKK'ını değerlendirdikleri çalışmalarında gruplar arasında fark olmadığını belirtirken, Ekinci ve ark., 107 OUAS hastasını incelemiş ve uyku apnesinin MKK'de incelmeye neden olduğunu bildirmişler-dir. 9,18 Araştırmacılar, OUAS'daki kornea incelmesinin apne atakları sırasında oluşan hipoksi ve hiperkapniye bağlı olarak meydana gelebileceğini belirtmişlerdir.…”
Section: İstati̇sti̇ksel Anali̇zunclassified